Hubungan Pola Makan dengan Kejadian Anemia pada Remaja Sekolah - Ruliyani, Hani; Amalia, Linda; Sulastri, Afianti (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2025)
One of the most common health problems among Indonesian adolescents is anemia. Adolescents are a group that is vulnerable to anemia because they are experiencing rapid growth and have high nutritional needs. An unbalanced diet, especially low iron intake, is one of the main factors contributing to the incidence of anemia. This study aims to evaluate the relationship between diet and the prevalence of anemia in junior high school students in Bandung City. A quantitative research design with a descriptive correlational approach and a cross-sectional design was conducted on 168 students of SMPN 20 Bandung City who were selected by cluster random sampling. Hemoglobin levels were measured using the Easy Touch Hb device, and food intake was assessed through the Food Frequency Questionnaire which had been tested for validity (r count r table = 0,361; n = 30) with a Cronbach's Alpha value = 0,917. Data analysis was performed using the Chi-Square test. This study found that 29,2% of respondents had anemia. Most students (57,1%) had poor diets. Adolescents who implemented a balanced diet showed a lower prevalence of anemia compared to adolescents who had poor diets. Intake of nutrients such as carbohydrates, proteins, fats, vitamins, minerals was found to be higher among the non-anemic group. Chi-Square test showed a statistically significant association between diet and anemia with a value of (p = 0,000; OR = 0,261). Poor eating habits were significantly associated with increased risk of anemia among adolescents. This study highlights the need for nutrition education programs in schools to promote balanced diet.